21 hari tebusan di Sierra Leone - Jaganathan, Ganase, 1958- (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2015)
Biography of Ganase Jaganathan, a Malaysian army officer during the revolutionary United Front in Sierra Leone.
Keywords: Jaganathan, Ganase, -- 1958- -- Biography; United Nations -- Peacekeeping forces -- Sierra Leone; Sierra Leone -- History -- Civil War, 1991-2002 -- Personal narratives, Malaysian